THU0683 Predictors for preterm delivery among pregnant women with rheumatoid arthritis and juvenile idiopathic arthritis. (12th June 2018) - Smith, C.J.F.; Förger, F.; Chambers, C.
Abstract : Background: It has previously been shown that pregnant women with inflammatory arthritis are at an increased risk for preterm delivery (PTD), yet it remains unclear what underlying maternal factors may drive this excess risk. Objectives: The aim of our study is to identify overall predictors for PTD among women with rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA) and to analyse the contribution of maternal disease activity, medication use, and comorbid pregnancy conditions on the risk for PTD in this population. Methods: Data were obtained from the Organisation of Teratology Information Specialists (OTIS) Autoimmune Disease in Pregnancy Project, a prospective cohort study among pregnant women in the U.S. and Canada. Women who enrolled between 2004 and 2017 prior to 19 weeks' gestation, had not enrolled with a previous pregnancy, and delivered at least one live born infant were considered eligible for analysis. All data were obtained by maternal report via telephone interviews and confirmed in the medical record when available. For our statistical analysis, Poisson regression with robust standard errors was used to estimate multivariable adjusted risk ratios. Results: Mothers with RA and JIA had a higher risk of PTD, preterm labour, early term delivery, and caesarian section versus comparison women. Women with RA additionally had a higher risk of gestational diabetes mellitus (GDM), and women with JIA had a higher risk of preeclampsia versus the comparison group. Active disease (defined as patient activity scale (PAS) score >3.70) was associated with PTD among women with RA both at intake and anytime during pregnancy, and this association remained after adjustment for corticosteroid (CS) use (aRR 1.60, 95% CI 1.12–2.30; aRR 1.54, 95% CI 1.08–2.20, respectively). CS use in all three trimesters was associated with PTD among women with both RA and JIA, an association that remained after multivariable adjustment for maternal factors including disease activity. Use of non-steroidal anti-inflammatory drugs (NSAIDs) in the first trimester was associated with PTD in women with JIA (aRR 2.31, 95% CI 1.04–5.14). Additional analysis showed that preeclampsia was associated with a higher risk of PTD among both RA and JIA women (aRR 1.92, 95% CI 1.12–3.31; aRR 3.01, 95% CI 1.10–8.23, respectively) but not in the comparison group. GDM and caesarian section were associated with a higher risk of PTD exclusively among RA women (aRR 1.84, 95% CI 1.07–3.15 and aRR 1.58, 95% CI 1.09–2.28, respectively) and fever during pregnancy increased the risk for PTD exclusively among women with JIA (aRR 3.45, 95% CI 1.47–8.08). Conclusions: Women with RA and JIA are at risk for preterm delivery. Maternal disease activity and medication use, particularly corticosteroid use, may explain much of this excess risk. Disclosure of Interest: None declared